Sustainable and smart spatial planning in Africa : case studies and solutions - Chavunduka, Charles; Vries, Walter Timo de; Duran Diaz, Pamela (Boca Raton : CRC Press, 2022)
"This book clarifies the smart city concept that is gaining application in Sub - Saharan Africa. It shows how the smart concept can be used to address problems that would be difficult and more expensive to solve using traditional techniques such as employment creation. This is done through elaboration of the African interpretation of smartness, using tools for smart solid waste management, e-governance, smart energy, and smart infrastructure. The case studies selected, and each chapter explain a different dimension of the smart city concept and offer innovative solutions to problems of rapid urbanization. It lays the theoretical foundation for further research on smart cities and rural areas in Africa"--
Sustainable and smart spatial planning in Africa : introduction -- Theory of sustainable and smart spatial planning -- Context and external drives of sustainable and smart spatial planing -- Goals and practice of sustainable and smart spatial planning -- Methods and tools for sustainable and smart spatial planning -- Future of sustainable and smart spatial planning in Africa.
OCLC-licensed vendor bibliographic record.
Keywords: Smart cities -- Africa; Sustainable urban development -- Africa; Land use -- Africa; TECHNOLOGY -- Remote Sensing; TECHNOLOGY -- Engineering -- Civil; ARCHITECTURE -- Urban & Land Use Planning; TECHNOLOGY / Remote Sensing; TECHNOLOGY / Engineering / Civil; ARCHITECTURE / Urban & Land Use Planning